Is Video-Assisted Thoracoscopic Surgery Adequate in Treatment of Pulmonary Hydatidosis? - LAÇİN, TUNÇ (ELSEVIER SCIENCE INC, 2015)
Background. Surgical management of pulmonary hydatid cyst disease has been well established. However, there are still limited data on the role of video-assisted thoracoscopic surgery in treatment of this disease. The aim of this study is to identify the advantages and disadvantages of minimally invasive surgery and compare the outcomes with patients undergoing thoracotomy in this parasitic disease. Methods. The medical records of 77 patients (53 male, 24 female) undergoing surgery for pulmonary hydatid cyst disease between January 2011 and January 2014 were reviewed. Removal of the hydatid cyst was completed using video-assisted thoracoscopic surgery in 39% (n = 30) of the patients, whereas open thoracotomy was used in 61% (n = 47). Conversion rate was 21%. Statistical analysis was used to assess differences in drainage amount, time to drain removal, length of surgery, length of hospital stay, and pain scores. Probability values of less than 0.05 were considered significant. Results. The drainage amount, time to drain removal, length of surgery, duration of narcotic analgesics usage, and visual analog scale scores in the thoracotomy group were significantly longer than those of the thoracoscopy group. Postoperative complications occurred in 4.3% of thoracotomy and in 13.3% of thoracoscopy patients. There was no mortality in either group. During the follow-up period, no recurrence was detected. Conclusions. Video-assisted thoracoscopy for surgery of pulmonary hydatid cyst disease is superior to open thoracotomy causing less postoperative pain, a better cosmetic result, a shorter surgical time, a lower drainage volume, and a shorter time to drain removal in a selected group of patients. The fear of recurrence because of incomplete isolation of the cyst during removal was not a concern regarding our technique. (C) 2015 by The Society of Thoracic Surgeons
Keywords: SURGICAL-TREATMENT; LUNG; EXPERIENCE; DISEASE; CYST; REMOVAL